2017
DOI: 10.1016/j.yexmp.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autoimmune myocarditis by host responses to the microbiome

Abstract: The extensive, diverse communities that constitute the microbiome are increasingly appreciated as important regulators of human health and disease through inflammatory, immune, and metabolic pathways. We sought to elucidate pathways by which microbiota contribute to inflammatory, autoimmune cardiac disease. We employed an animal model of experimental autoimmune myocarditis (EAM), which results in inflammatory and auto-immune pathophysiology and subsequent maladaptive cardiac remodeling and heart failure. Antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The gut microbiota is a complex ecosystem of symbiotic bacteria. It contributes to the mammalian host physiology and metabolism by (i) aiding the processing of the apparently indigestible nutrients, (ii) supplying the necessary metabolites, and (iii) activating the host's protective immune system to some extent [19,20]. Macrophages, neutrophils, monocytes, innate lymphoid cells, and bacterial metabolism products like short-chain fatty acids (SCFAs) are known to inhibit the growth of pathogens by producing primary and secondary bile acids, and butyrate [21].…”
Section: The Gut Microbiome and The Protective Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…The gut microbiota is a complex ecosystem of symbiotic bacteria. It contributes to the mammalian host physiology and metabolism by (i) aiding the processing of the apparently indigestible nutrients, (ii) supplying the necessary metabolites, and (iii) activating the host's protective immune system to some extent [19,20]. Macrophages, neutrophils, monocytes, innate lymphoid cells, and bacterial metabolism products like short-chain fatty acids (SCFAs) are known to inhibit the growth of pathogens by producing primary and secondary bile acids, and butyrate [21].…”
Section: The Gut Microbiome and The Protective Immunitymentioning
confidence: 99%
“…Alteration/changes within the gut microflora may pose significant impact on the regulation of host biochemical and metabolic design. The knowledge on (i) gut microflora, (ii) associations between the microbiome and the inflammasome, (iii) the innate immune system, (iv) role of bile acids, (v) the gut permeability may aid potential preventive strategy against CVD and coupling microorganisms to the pathogenesis of the autoimmune disease [19,[35][36][37][38][39]. Indeed, the gut microorganisms are one of the important main factors influencing systemic immune responses and metabolic dysfunctions among the individuals with obesity.…”
Section: How the Gut Microbiome Triggers Cvd?mentioning
confidence: 99%
See 1 more Smart Citation
“…Barin JG showed that gut microbial dysbiosis may trigger autoimmune myocarditis and it may lead to subsequent maladaptive cardiac remodeling and heart failure. So, we can conclude that gut microbiota have a significant impact on the cardiac function by the distant immugenic effects [ 47 ].…”
Section: Pathophysiology Of Microbial Agents and Linkage To Atheromentioning
confidence: 99%
“…Similarly, in animal models of experimental autoimmune myocarditis, an increase in microbial diversity and richness has been observed [ 9 ]. Interestingly, it was also observed that in different mice with different gut microbiota colonization profiles, susceptibility to autoimmune myocarditis varied immensely [ 10 ].…”
Section: Introduction: Microbiota and The “Heart–gut Axis”mentioning
confidence: 99%